anfaatan Video Tiktok Sebagai Media Pembelajaran Menulis Teks Eksplanasi Peserta Didik Kelas VIIISMPN31 Semarang Tahun Ajaran 2022/ 2023 - Hasan Arafat; Mukhlis Mukhlis; Suyoto Suyoto (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The background of this research is that the activities of Class VIII students of SMPN 31 Semarang in the learning process are not enthusiastic, students only focus on using books as learning aids. Therefore, in the learning process we need a media-based learning aid that can attract students' attention in order to improve student performance and understanding. It is important to apply TikTok-based learning application innovations to involve students in learning so that the material being taught is easy to understand.    Based on this background, the problem arises How to Use the Tiktok Application as a Learning Media in Writing Explanatory Text Writing Skills for Class VIII Students of SMPN 31 Semarang Academic Year 2022/2023? This study aims to identify the Utilization of the Tiktok Application as a Learning Media in Writing Explanatory Text Writing Skills for Class VIII Students of SMPN 31 Semarang Academic Year 2022/2023. This type of research is mixed method . Data collection was carried out by observation, interview, test and documentation methods.    The results of this study indicate that students in class VIII use the media using the social media application TikTok above, it can be seen that the average score of students in class VIII SMPN 31 Semarang in the 2022/2023 academic year when writing explanatory texts in general is at the moderate level (50- 74). The average score of the students on the explanatory text writing test performance was 66.71 at the sufficient level.